Characteristics, management, and outcomes of patients with left-sided infective endocarditis complicated by heart failure: a substudy of the ESC-EORP EURO-ENDO (European infective endocarditis) registry - MUTLU, BÜLENT (My University, 2022)
Aims To evaluate the current management and survival of patients with left-sided infective endocarditis (IE) complicated by congestive heart failure (CHF) in the ESC-EORP European Endocarditis (EURO-ENDO) registry. Methods and results Among the 3116 patients enrolled in this prospective registry, 2449 (mean age: 60years, 69% male) with left-sided (native or prosthetic) IE were included in this study. Patients with CHF (n = 698, 28.5%) were older, with more comorbidity and more severe valvular damage (mitro-aortic involvement, vegetations >10 mm and severe regurgitation/new prosthesis dehiscence) than those without CHF (all p 10 mm, severe valvular regurgitation and/or new prosthetic dehiscence, perivalvular complication, and prosthetic IE (OR 0.22, 95% CI 0.12-0.38; p < 0.001) and in 1-year mortality (HR 0.29, 95% CI 0.20-0.41; p < 0.001). Conclusion Congestive heart failure is common in left-sided IE and is associated with older age, greater comorbidity, more advanced lesions, and markedly higher 30-day and 1-year mortality. Early surgery is strongly associated with lower mortality but is performed on only approximately half of patients with CHF, mainly because of a surgical risk considered prohibitive.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Kardiyoloji; Medicine; Health Sciences; Internal Medicine Sciences; Cardiovascular; KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; Infective endocarditis; Congestive heart failure; Survival; Outcome; Early surgery; EURO-ENDO; NATIVE VALVE ENDOCARDITIS; PROGNOSTIC-FACTORS; MORTALITY; SURGERY; RISK; PREDICTORS; ADULTS; IMPACT; DEATH; Infective endocarditis; Congestive heart failure; Survival; Outcome; Early surgery; EURO-ENDO